The Role of Sociodemographic Factors on Physical Activity and Obesity in Individuals with Type 2 Diabetes: A Descriptive-Cross-Sectional Study - Yiğiter, Nuray; Akçınar, Faruk; Yılmaz, Büşra; Yasul, Muhammet Enes; Yasul, Yavuz (İnönü Üniversitesi, 2025)
Objective: Type 2 diabetes mellitus (T2DM) is a common metabolic disorder characterized by insulin resistance and beta cell dysfunction. Body mass index (BMI) and physical activity level (PAL) are considered to be decisive indicators in the progression and management of the disease. The aim of this study is to investigate the effects of BMI and PA levels on various sociodemographic variables in individuals diagnosed with T2DM. Method: This study is a descriptive research designed in a cluster model. It included 306 volunteers aged 18 years and older who had been diagnosed with type 2 diabetes. Data were collected using the International Physical Activity Questionnaire-Short Form (IPAQ-SF) and a sociodemographic information form developed by the researchers. Participants' height and weight measurements were taken, and their BMI values were calculated. Data were analyzed using parametric tests, including the independent samples t-test, one-way analysis of variance (ANOVA), and Tukey HSD test to determine significant differences, with a statistical significance level of p0.05); however, female participants had significantly higher BMI values than males (p=0.036). Individuals using only oral antidiabetic drugs or only insulin had higher FAD scores than those using both treatments together. FAD increases with education level; high school and university graduates show similar levels of activity. Single individuals have both higher FAD levels and lower BMI values compared to married individuals. FAD decreases with age, while BMI increases. A significant difference was found between educational status and BMI; particularly, the BMI values of elementary school graduates in the obese group were higher than those of other groups (p

Amaç: Tip 2 diyabet mellitus (T2DM), insülin direnci ve beta hücre disfonksiyonu ile karakterize edilen yaygın bir metabolik bozukluktur. Beden kitle indeksi (BMI) ve fiziksel aktivite düzeyi (FAD), hastalığın ilerleyişi ve yönetiminde belirleyici göstergeler olarak değerlendirilmektedir. Bu çalışmanın amacı, T2DM tanısı almış bireylerin BMI ve FAD düzeylerinin çeşitli sosyodemografik değişkenler üzerindeki etkilerini incelemektir. Yöntem: Bu çalışma, betimsel bir araştırma olup küme modelinde tasarlanmıştır. Tip 2 diyabet teşhisi almış, 18 yaşı tamamlamış ve üzeri yaş grubunda bulunan 306 gönüllü birey dâhil edilmiştir. Veriler, Uluslararası Fiziksel Aktivite Anketi-Kısa Form (IPAQ-SF) ve araştırmacılar tarafından geliştirilen sosyodemografik bilgi formu ile toplanmıştır. Katılımcıların boy ve kilo ölçümleri yapılarak BMI değerleri hesaplanmıştır. Veriler, parametrik testler kapsamında bağımsız örneklem t-testi, tek yönlü varyans analizi (ANOVA) ve anlamlı farklılıkların belirlenmesi amacıyla Tukey HSD testi kullanılarak analiz edilmiş, istatistiksel anlamlılık düzeyi p0.05); ancak kadın katılımcıların BMI değerleri erkeklere kıyasla anlamlı düzeyde daha yüksektir (p=0.036). Sadece oral antidiyabetik ya da yalnızca insülin kullanan bireylerin FAD puanları, her iki tedaviyi bir arada kullananlara kıyasla daha yüksektir. Eğitim düzeyi arttıkça FAD da artmakta; lise ve üniversite mezunları benzer düzeyde aktivite göstermektedir. Bekar bireyler, evlilere kıyasla hem daha yüksek FAD düzeyine hem de daha düşük BMI değerine sahiptir. Yaş ilerledikçe FAD azalırken, BMI artmaktadır. Eğitim durumu ile BMI arasında anlamlı fark tespit edilmiştir; özellikle obez grubunda yer alan ilkokul mezunlarının BMI değerleri diğer gruplara göre daha yüksektir (p
Tip 2 Diyabetli Bireylerde Fiziksel Aktivite ve Obezite Üzerine Sosyodemografik Etkenlerin Rolü: Tanımlayıcı-Kesitsel Bir Çalışma
Keywords: Physical Activity and Health; Fiziksel Aktivite ve Sağlık